Bone marrow-derived macrophages incorporate into the endothelium and influence vascular and renal function after irradiation. (September 2014) - de Cortie, Karin; Russell, Nicola S.; Coppes, Rob P.; Stewart, Fiona A.; Scharpfenecker, Marion
Abstract Purpose: We recently demonstrated that endoglin, an ancillary transforming growth factor beta (TGF-β) receptor, modulates vascular damage and fibrosis formation and influences renal function after kidney irradiation. We also suggested that this was partially accomplished by endoglin-mediated regulation of cytokine production in macrophages. Endoglin is expressed on both endothelial cells and on activated macrophages. Therefore, in the current study, we addressed the respective contribution of altered endoglin levels in the different cellular compartments to the development of kidney toxicity after irradiation. Materials and methods: Female endoglin wild-type (Eng+/+ or WT) or heterozygous (Eng+/− or HET) mice were subjected to total body irradiation (2 × 6 Gy with a 6-hour interval) followed by kidney irradiation (1 × 3 Gy). Recipient mice were then transplanted with 4 × 10E6 green fluorescent protein heterozygous (GFP+/−) bone marrow cells from either Eng+/+ or Eng+/− male donor mice. Chimerism was determined 6 weeks thereafter. Blood samples were taken every 10 weeks after irradiation and at sacrifice at 35 weeks. One kidney was used to isolate macrophages; the other kidney was used for histology and to determine cytokine and chemokine concentrations. Results: In all treatment groups, the majority of infiltrating macrophages were bone marrow-derived and this was not altered by endoglin. Bone marrow cells accumulated in damaged tissue areas in the interstitium, but also incorporated into the vasculature. Reducing endoglin levels in macrophages, but not in the endothelium, led to improved renal function (hematocrit, blood urea nitrogen) after irradiation. This was probably promoted by lowered production of pro-inflammatory cytokines and chemokines in macrophages. Other measurements of tissue toxicity (pericyte coverage, fibrosis, damage score) were not altered by differential endoglin expression. Conclusions: Endoglin regulates pro-inflammatory macrophage properties thereby influencing vascular and renal function after kidney irradiation.